Drivers of yeast community composition in the litter and soil of a temperate forest - Mašínová, Tereza; Bahnmann, Barbara Doreen; Větrovský, Tomáš; Tomšovský, Michal; Merunková, Kristina; Baldrian, Petr (FEMS microbiology ecology, 2017)
Fungi represent a group of soil microorganisms fulfilling important ecological functions. Although several studies have shown that yeasts represent a significant proportion of fungal communities, our current knowledge is based mainly on cultivation experiments. In this study, we used amplicon sequencing of environmental DNA to describe the composition of yeast communities in European temperate forest and to identify the potential biotic and abiotic drivers of community assembly. Based on the analysis of ITS2 PCR amplicons, yeasts represented a substantial proportion of fungal communities ranging from 0.4 to 14.3% of fungal sequences in soil and 0.2 to 9.9% in litter. The species richness at individual sites was 28 ± 9 in soil and 31 ± 11 in litter. The basidiomycetous yeasts dominated over ascomycetous ones. In litter, yeast communities differed significantly among beech-, oak- and spruce-dominated stands. Drivers of community assembly are probably more complex in soils and comprise the effects of environmental conditions and vegetation.
Keywords: Fagus; buk (rod); Soil; Trees; Forests; houby; kvasinky; biodiverzita; Yeasts; půdní mikrobiologie; Soil Microbiology; lesy; Fungi; Picea; smrk; Saccharomyces cerevisiae; stromy; půda; Biodiversity